Qualitative Research: The Contributing Factors And Coping Strategies On Suicidal Ideation Among University Students - Qurra Ta Ayunin, Muhamad Zamry (Universiti Malaysia Sarawak (UNIMAS), 2022)
Background: Suicidal ideation is a negative thinking about wanting to die with no planning of attempting suicide. In Malaysia, there are a lot of research related with suicidal ideation yet the information on suicidal ideation among university student is limited. Other than that, the contributing factors on suicidal ideation and coping strategies on suicidal ideation among university student also is not discussed. Objectives: To understand the phenomenon of suicidal ideation among university students, to identify the contributing factors of suicidal ideation among university students and to explore the coping strategies on suicidal ideation among university students. Method: The sampling method that were used is the purposive sampling where five university students from the University of Malaysia, Sarawak were interviewed using semi-structured interview. Results: Based on the finding, the theme for the phenomenon on suicidal ideation among university student are time and the subthemes are periods, frequency, and duration. The theme for the contributing factors on suicidal ideation is family factors with parent-child relationship and family conflict as the subthemes, then the theme emotional distress with hopelessness and loneliness as the subthemes, and the theme life events with negative life events as the subthemes. The theme for coping strategies on suicidal ideation are healthy coping strategies with distraction, talking and self-love as the subthemes and unhealthy coping strategies with drinking and smoking as the subthemes.